Accounting standards and German supplementary pensions: the emergent framework underpinning global finance - Mansfield, D; Tickell, A; Clark, G (Clark University, MA, USA, 2001)
Adoption of international and U.S. financial accounting standards by leading German corporations presages a new era in European capital markets, with important implications for the design and management of German supplementary pensions. In this paper, we first introduce financial accounting standards boards, the evolution of U.S. pension accounting standards since ERISA (1974), and the introduction of FASB 87. We emphasize the quiet campaign by national and international accounting professionals to harmonize corporate accounting and the measurement of pension liabilities to accepted international standards. Using data collected from 1998 annual reports for German firms in the DAX 30 index, we report on and explain the adoption of international accounting standards by large German firms. This takes us to an analysis of the scope and significance of corporate pension liabilities. Noting the connection between accounting standards and global capital markets, we identify the implications of harmonization of German supplementary pension and retirement benefit systems for the mechanisms of financing benefits, the valuation of assets and liabilities, and the advantages and disadvantages of defined benefit as opposed to defined contribution plans. In combination, we show that historical differences between the Anglo-American system of corporate governance and the German system of entrenched management within interlocking boards of supervision and the representation of stakeholders' interests are now less compelling than assumed.